Pembelajaran Daring dan Motivasi Belajar Peserta Didik Ditengah Wabah COVID-19 - Syarifah Syarifah; Ayu Lestari; Nurhaliza Nurhaliza; Yuni Anggaraini; Hakmi Wahyudi; M. Fahli Zatrahadi (Lembaga penelitian dan pengabdian kepada masyrakat, 2022)
The purpose of this study was to analyze the effect of the learning system on students' learning motivation. The method used in this research is the study of literature or literature using secondary data sources. In this study, data collection was obtained from news and online articles. Data testing for data effectiveness is carried out using the steps of data collection, data reduction, data visualization, and conclusions. The results of this study indicate that the learning system has an effect on students' learning motivation. Students can become less active in conveying their aspirations and thoughts, so that it can lead to boring learning. A student who experiences boredom in the teaching and learning process will get progress in learning outcomes. The impact of bold learning should be of concern to everyone involved in the educational process, including government, educators, students and parents. Therefore, there is a need for a solution so as not to hinder the coaching and motivation of students when learning online. Some solutions to solve the influence of bold learning include: increasing the educational capacity and computer skills of teachers, Using suitable learning methods for online learning and supporting internet quotas.